2023
DOI: 10.3390/ijms24021060
|View full text |Cite
|
Sign up to set email alerts
|

Initial Investigations of Intrinsically Disordered Regions in Inherited Retinal Diseases

Abstract: Intrinsically disordered regions (IDRs) are protein regions that are unable to fold into stable tertiary structures, enabling their involvement in key signaling and regulatory functions via dynamic interactions with diverse binding partners. An understanding of IDRs and their association with biological function may help elucidate the pathogenesis of inherited retinal diseases (IRDs). The main focus of this work was to investigate the degree of disorder in 14 proteins implicated in IRDs and their relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The highest number of occurrences was in the 0 to 10th disorder decile, and the lowest distribution was in the 90th to 100th disorder decile. We previously showed that proteins with a high degree of disorder tolerated the greatest amount of missense variation [ 4 ], so we plotted the percent disorder of all proteins in the RetNet Database with respect to the total number of missense variants ( Figure 2 ). Regression analysis between disorder and total missense variants showed R = 0.079 and p = 0.18, between percent disorder and percent pathogenicity showing R = 0.024 and p = 0.68, as well as between % total missense and % disorder showing R = 0.062 and p = 0.301.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The highest number of occurrences was in the 0 to 10th disorder decile, and the lowest distribution was in the 90th to 100th disorder decile. We previously showed that proteins with a high degree of disorder tolerated the greatest amount of missense variation [ 4 ], so we plotted the percent disorder of all proteins in the RetNet Database with respect to the total number of missense variants ( Figure 2 ). Regression analysis between disorder and total missense variants showed R = 0.079 and p = 0.18, between percent disorder and percent pathogenicity showing R = 0.024 and p = 0.68, as well as between % total missense and % disorder showing R = 0.062 and p = 0.301.…”
Section: Resultsmentioning
confidence: 99%
“…The Mane Select transcript was selected for each protein. The sequences were then run through Metapredict (version 2.3) to plot the intrinsically disordered regions (IDRs) as previously described [ 4 ]. Because multiple predictors are available, consensus scores have emerged to interpret the outcomes of multiple independent disorder predictors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations